Kann Man Rechtstexte kulturell einbetten? - Kocbek, Alenka (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2010)
In many aspects, legal translation seems to be an adequate domain for applying the principles of the functionalist approaches to translation, especially the skopos-theory by J. H. Vermeer. Nevertheless, an indiscriminate application of the principle of cultural embeddedness could prove questionable, if not misleading, as it may cause disturbance in the legal communication occurring through the translation act. In some legal transactions, such as e.g. international contracts, involving contracting parties belonging to different nations, only one legal system is adopted as the communication framework (i.e. the governing or applicable law). In such cases, the functionalist principle of cultural embeddedness needs to be applied selectively, i.e. only with respect to some linguistic features of the text, while in a broader sense, as far as the cultural and/or legal foundations of the text are concerned, the source and the target text will have the same reference frame.

Pravna besedila se glede na svojo naravo zdijo posebej primerna za uporabo funkcionalističnih prevodoslovnih pristopov, posebej teorije skoposa. Vendar pa se dosledna uporaba načela kulturne vpetosti jezika lahko izkaže kot neprimerna ali celo zavajajoča, ker lahko povzroči motnje v pravnem sporazumevanju, ki poteka preko prevajalskega dejanja. Pri nekaterih pravnih poslih kot npr. pri pogodbah, v katerih so udeležene stranke iz različnih držav, se kot komunikacijski okvir določi en sam pravni sistem (t.i. merodajno ali veljavno pravo). V takńnih primerih je mogoče načelo kulturne vpetosti uporabiti samo glede na lingvistične vidikih besedila, v ńirńem obsegu, t.j. kar zadeva kulturno oz. pravno podlago besedila, pa imata izhodińčno in ciljno besedilo isti referenčni okvir.

Unter vielen Aspekten scheint sich die Rechtsübersetzung besonders gut zur Anwendung der Prinzipien der funktionalistischen Translationsansätze, besonders der Skopos-Theorie von J.H. Vermeer, zu eignen. Jedenfalls kônnte sich eine konsequente Durchsetzung des Prinzips der kulturellen Einbettung als unangebracht, sogar als irreführend erweisen, da sie zu Stôrungen in der durch die Translationshandlung stattfindenden Rechtskommunikation führen kann. In einigen Rechtsgeschäften, wie z.B. in Verträgen, an denen Vertragsparteien aus verschiedenen Staaten beteiligt sind, wird nur ein Rechtssystem als Kommunikationsrahmen definiert (das sog. maßgebende bzw. anwendbare Recht). In solchen Fällen kann man das Prinzip der kulturellen Einbettung nur mit Bezug auf die linguistischen Aspekte des Textes anwenden, in weiterem Ausmaß, d.h. was die Kultur- bzw. Rechtsgrundlage des Textes betrifft, haben aber der Ausgangs- und der Zieltext den selben Referenzrahmen.
Can legal texts be culturally embedded?